30th AIAA Applied Aerodynamics Conference 2012
DOI: 10.2514/6.2012-3206
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of The Upper Surface of An Airfoil By Macro Fiber Composite Actuators

Abstract: In this follow-on study, macro fiber composite actuators are used to change the shape of the upper surface of an airfoil model with geometry close to that of the NACA 4415 type. In the design discussed, these thin and light piezoelectric actuators are bonded to the inside and become an integral part of the skin of the upper surface of the airfoil. The model used in this study incorporates some structural changes that allow a smoother shaping of the surface closer to the leading edge of the airfoil. Still-air a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Finally, in addition to the current application, the presented design can be used for optimal aerodynamic shaping of a wing at other flight conditions [43,44]. In fact, suitable input signals would allow periodic surface morphing to be superimposed to aerodynamic shaping thus simultaneously providing two types of aerodynamic control with one actuator.…”
Section: Control Efficiencymentioning
confidence: 99%
“…Finally, in addition to the current application, the presented design can be used for optimal aerodynamic shaping of a wing at other flight conditions [43,44]. In fact, suitable input signals would allow periodic surface morphing to be superimposed to aerodynamic shaping thus simultaneously providing two types of aerodynamic control with one actuator.…”
Section: Control Efficiencymentioning
confidence: 99%
“…, ' c io , and ' G io are the phase margin of the system, phase margin of current controller, and phase margin of the system described by equation (11). Figure 6 shows the loop scheme of the current controller, while Figure 7 depicts the system response for a step current value of 0.928 A.…”
Section: Control System Design and Analysismentioning
confidence: 99%
“…The piezoelectric actuators were bonded to the inside and became an integral part of the airfoil flexible skin. This study was performed in two phases, the first one assumed the actuation of the upper surface of the airfoil, 11 while the second one assumed the actuation of both upper and lower surfaces of the airfoil. 12 The results from wind tunnel tests concluded that this kind of morphing wings may be used successfully for maneuvering the wings without ailerons, and/or for active control of the flow over the wing in order to have an aerodynamic efficiency improvement.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical design previously presented by Debiasi et al 23,24 is applied in this study to both the upper and the lower surfaces on an airfoil. However some improvements have been made to address the shortcomings and enhance the dynamic response observed in a previous type.…”
Section: Introductionmentioning
confidence: 99%